University students' difficulties in solving application problems in calculus: student perspectives - Klymchuk, S; Zverkova, T; Gruenwald, N; Sauerbier, G (Mathematics Education Research Group of Australasia (MERGA), 2010)
This paper reports on the results of an observational parallel study conducted simultaneously at 2 universities – one each in New Zealand and Germany. It deals with university engineering students’ difficulties in the formulation step of solving a typical application problem from a first-year calculus course. Two groups of students (54 in New Zealand and 50 in Germany) completed a questionnaire about their difficulties in solving the problem which was set as part of a mid-semester test. The research endeavoured to find reasons most of the students could not use their knowledge to construct a simple function in a familiar context. It was neither lack of mathematics knowledge nor an issue with the context. The students’ difficulties are analysed and presented along with their suggestions on how to improve their skills in solving application problems.